High Dose Intramuscular Vitamin D3 Supplementation Impacts the Gut Microbiota of Patients With Clostridioides Difficile Infection - Lee, Sang Hoon; Park, Han-Ki; Kang, Chang Don; Choi, Dae Hee; Park, Sung Chul; Park, Jin Myung; Nam, Seung-Joo; Chae, Gi Bong; Lee, Kyoung yul; Cho, Hyunseok; Lee, Sung Joon (Frontiers in Cellular and Infection Microbiology, 2022)
Background and Aim: Current therapeutic strategies for Clostridioides difficile infections (CDI), including oral vancomycin, metronidazole and fecal microbial transplantation, have limited efficacy and treatment failure may occur in as many as one- third of cases. However, the exact relationship between vitamin D deficiency and CDI remains unclear. Using 16S rRNA microbial profiling, our study aimed to compare the microbiota composition between the two groups, including eight CDI-positive patients with vitamin D supplementation and ten CDI-positive patients without vitamin D supplementation. Methods: Twenty subjects were enrolled in this prospective randomized controlled study. One subject dropped out due to lack of contact with the guardian after discharge and one subject dropped out due to withdrawal of consent. Thus, 18 patients with CDI and vitamin D insufficiency (vitamin D level < 17) were divided into two groups: CDI with vitamin D supplementation (n = 8) and CDI without vitamin D supplementation (control: n = 10). Subjects with vitamin D insufficiency were randomized to receive 200,000 IU intramuscular cholecalciferol. Stool samples were obtained at diagnosis and eight weeks after treatment; 16S rRNA metagenomic sequencing was performed using EzBioCloud. Results: The alpha diversity of the gut microbiota in the recovery state was significantly higher than that in the CDI state. Analysis of bacterial relative abundance showed significantly lower Proteobacteria and higher Lachnospiraceae, Ruminococcaceae, Akkermansiaceae, and Bifidobacteriaceae in the recovery state. When comparing the control and vitamin D treatment groups after eight weeks, increase in alpha diversity and, abundance of Lachnospiraceae, and Ruminococcaceae exhibited the same trend in both groups. A significant increase in Bifidobacteriaceae and Christensenellaceae was observed in the vitamin D group; Proteobacteria abundance was significantly lower in the vitamin D treatment group after eight weeks than that in the control group. Conclusion: Our study confirmed that the increase in Bifidobacteriaceae and Christensenellaceae abundance were prominently evident during recovery after administration of a high dose of cholecalciferol. These findings indicate that vitamin D administration may be useful in patients with CDI, and further studies with larger sample sizes are required.